Breastfeeding experiences among mothers living with food insecurity in high resource, Western countries: a qualitative systematic review protocol. Issue 3 (16th March 2021) - Sim, Sarah Meaghan; Rothfus, Melissa; Aston, Megan; Kirk, Sara F.L.; Frank, Lesley; Jefferies, Keisha; Macdonald, Marilyn
ABSTRACT: Objective: The objectives of this review are to identify, appraise, and synthesize the qualitative evidence on the breastfeeding experiences of mothers living with food insecurity in high-resource, Western countries. Introduction: Breastfeeding and food insecurity are inter-related health issues. Globally, breastfeeding augments food security at individual, household, and community levels, but a growing body of evidence from high-resourced countries also suggests that a mother's breastfeeding practice may be negatively impacted by the additional experience of food insecurity. This protocol outlines a systematic approach to understanding the experiences of breastfeeding from the perspective of mothers living with food insecurity. Findings will provide much-needed evidence toward guiding policies and practices that support mothers to breastfeed. Inclusion criteria: The review will consider studies that explore the breastfeeding experiences of mothers aged 18 years and older who self-identify, or are classified using a screening tool, as food insecure. Papers that will be included in this review will consider all qualitative methodologies and will be limited to studies from countries identified as being within the United Nations classification of Western European and Other States Group (WEOG). Methods: The authors will conduct a three-step search process across both published and gray literature to identify relevant studies for inclusion. A preliminary search using the PubMed database was undertaken in January 2020. Studies published in English from 1981 to 2020 will be included. The recommended JBI methodology for qualitative systematic review for study selection, critical appraisal, data extraction, and data synthesis will be followed. Systematic review registration number: PROSPERO CRD42020183652